Sleep-Related Eating Disorder Induced by Olanzapine - Vincent Paquet; John Strul; Laurent Servais; Isidore Pelc; Pierre Fossion (2002)
Article Abstract Letter to the Editor Sir: Sleep-related eating disorder (SRED) is a recently described syndrome combining features of sleep disorders and eating disorders. This disorder consists of partial arousal from sleep followed by rapid ingestion of food, commonly with at least partial amnesia for the episode the following day. As reviewed by Schenck and Mahowald, the most frequent disorders responsible for SRED are sleepwalking, sleepwalking combined states (e.g., combined with amitriptyline treatment or periodic limb movement), restless legs syndrome, obstructive sleep apnea, eating disorders, and triazolam abuse.